Economic Impact of Crop Diversification in North-East India: Evidence from Household-level Survey - Priscilla, Laishram; Kar, Priyajoy; Krishnadas, Oinam; Nivetina, Laitonjam; Sharma, Ph Romen (Indian Journal of Extension Education, 2021)
The study used a large farm household level data to assess the economic impact of cropÂ diversification and also identifies the factors influencing the extent of diversification in the north east region of India. The crop sector was found to be skewed towards specialization.Â The result of instrumental variable technique showed that crop diversification has a positively significant impact on the income among the households. Further, fractional logit estimation found that variables like family members in the working age group, landholdingÂ size, crop loss experience, extension contact, participation in training positively affected diversification. Irrigated area, access to institutional credit, etc negatively affected the same. Diversification towards high value crops may accelerate the agricultural growth of the regionÂ and improve the wellbeing of the farmers. Measures for improvement of basic infrastructural facilities and extension services for improving backward and forward linkages are required.